The impact of novel COVID-19 initial pandemic on orthopedic healthcare: an experience from a single institution of South Korea - Lee, Gun Woo; Kim, Gi Beom; Lee, In Jun (Taehan Ŭisa Hyŏphoe chi, 2021)
Background: This study was to investigate the cancellation rate and trend of orthopedic surgeries during the novel coronavirus disease 2019 (COVID-19) pandemic. Moreover, we assessed the psychologic status of orthopedic healthcare workers, and investigated the details of the preventive surgeries underwent in COVID-19-positive patients.Methods: For 3 months after January 20, 2020, cancellation rates of elective surgeries were investigated, and the number of elective surgeries conducted in the same period over the last two years was compared. Four different questionnaires were used to investigate psychologic status among the orthopedic health care workers. We compared the outcomes according to occupation (physician or nurse), and type of work (faculty staff or resident physician). Outcomes according to occupation and type of work were compared. Preventive surgeries underwent in patients who could not wait for the results of the COVID-19 diagnosis were investigated.Results: Spine and hip surgery had relatively lower cancellation rates, and elective surgeries were significantly reduced. During the initial pandemic, the cancellation rate of orthopedic elective surgeries was significantly higher than in the same period of the previous year and was different for each subdivision depending on the degree of pain or disability. The psychological outcomes were within the normal range and there were no significant differences between groups. After preventive surgery, all medical staff involved in the operation tested negative.Conclusion: During the COVID-19 pandemic, the cancellation rate of orthopedic elective surgeries was significantly higher than in the same period of the previous year. Orthopedic health care workers did not seem to have significant psychological distress. As a result of the preventive surgery in specialized facilities, all the medical staff who participated in the operation tested negative.